Health and beauty - the lasting solution, 1987 (1987)
1987 1960-2000 "Health and beauty - the lasting solution, 1987" [EP0151], 1987 This union recruitment leaflet issued by the Southwark Trade Union Support Unit in 1987 uses similar arguments to those issued by trade unions in the 1930s.